The Effect of Work Overload on Job Performance with Emotional Exhaustion as Mediating Variable (Study at Employee of Production Department PT. ROYAL KORINDAH Purbalingga) - Astuti, Novi; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2018)
The purpose of this study was to deteminate the influence of work overload on job performance the mediating of emotional exhaustion. The population of this study is employees of PT. Royal Kotindah Purbalingga. A total samples is 96 employees, and used proportionate random sampling. Methods of data collection used documentation    and quetionnaires. Methos of data analysis used descriptive analysis, classical assumption test, regression analysis, and path analysis. Data analysis used SPSS softwere for windows version 21. The result of this study show that work overload and emotional exhaustion have a negatiff significant effect on job performance. In addition, the result also show that work overload have a positive significant on emotional exhaustion. Futhermore, this study finds that emotional exhaustion mediates the relationship work overload on job performance.